Bioaerosol in dental prosthodontics - Jovanović Marija G. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2020)
Introdution: During many dental interventions, performed using handpiece instruments and pusters, an aerosol is created,which is converted into a bioaerosol (BIOA) by mixing with the particles of various organic components from the patient's oral cavity.When the high-speed mashine is started, the air becomes instantly contaminated and practically covers the entire room. Pollution is registered all the times, as well as after prosthetic treatment. BIOA created during prosthetic workcontains various bacteria, fungi and viruses from the patient's oral cavity. These microorganisms pose a real hazard to health workers and are a potential risk for infection. The most common pathogens include influenza viruses, herpes viruses, as well as pathogenic streptococci and staphylococci. Infectious diseases, biosynosis, acute toxic reactions, allergies, atopic diseases, conjunctivitis, contact dermatitis, infections of the respiratory system, and even some types of cancer, are possible manifestations of side effects of BIOA. Conclusion:BIOA poses a potential danger to contamination of air, work surfaces and objects in dental offices. Direct and indirect exposure of dental staff and patients to BIOA is especially pronounced in the conditions of COVID 19. Although it is impossible to completely eliminate the risk of adverse effects of BIOA, it is important to pay attention to all prevention measures that can reduce the likelihood of contamination.